On the definition of infodemic and the role of librarians: a conversation with Tina Purnat of WHO - Matilde Fontanin (AIB Studi, 2023)
If in 2017 the buzzword was ‘fake news’, since 2020 it was replaced by ‘infodemic’, a different phenomenon, yet connected to information disorder. In 2020, the World Health Organization (WHO) opened a call for a training for infodemic managers, within the strategy to counter Covid-19. Tina Purnat is Team Lead for Infodemic Management, Epidemic and Pandemic Preparedness and Prevention at WHO and, with a background in medical informatics, among librarians she feels at home.